Effect of Pine Wood Shavings, Rice Hulls and River Bed Sand on Broiler Productivity When Used as a Litter Sources - Atencio, J.L.; Fernandez, J.A.; Gernat, A.G.; Murillo, J.G. (International Journal of Poultry Science, 2010)
As the poultry industry has grown and expanded and as alternative uses of wood by-products have expanded, the availability of wood shavings and sawdust for litter materials has been challenged. Litter type utilized is largely dependent upon local availability of the material and location of the farm. Unfortunately, the availability of pine shavings has steadily decreased due to competition for its use from other industries and use as an energy source. The objective of this research was to evaluate conventional litter sources to sand as a substitute litter. For the experiment Pine Wood Shavings (PWS), Rice Hulls (RH), River Bed Sand (S) and river bed sand top dressed with pine wood shavings (SP) were the four litter source treatments implemented. Chicks were identified and randomly allocated in a randomized complete block design. Litter temperatures were recorded prior to bird placement. Body weight, cumulative feed consumption, feed conversion (feed: body weight) and litter moisture were determined on a weekly basis through 42 days of age. Mortality was recorded daily. At processing carcass weight, percentage carcass yield without giblets and gizzard yield were determined on a prechilled basis. Litter surface temperatures were significantly (p<0.001) higher for PWS, RH and SP compared to just S alone. Broilers raised on S had significantly (p<0.001) higher body weights and consumed more feed than those raised on PWS or RH throughout the 42 days. No significant differences were found for feed conversion, mortality or carcass yield. Carcass weight and gizzard yield were significantly (p<0.001) higher for birds raised on S. Sand maintained approximately 15% lower moisture level in comparison to PWS and RH and a 5% difference to SP (p<0.001). In conclusion, sand can potentially be used as an alternative litter material for growing broilers.